2021
DOI: 10.21470/1678-9741-2020-0521
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Oxygen Saturation/Lactate Ratio and Prediction of Major Adverse Events after Pediatric Heart Surgery

Abstract: Introduction Major adverse events (MAE) are unexpected but undesirably frequent after pediatric congenital heart surgery and contribute to poorer outcomes. The aim of this study was to test the predictive value of a ratio between central venous oxygen saturation and arterial lactate (ScvO2/lactate) for MAE after pediatric congenital heart surgery in a Brazilian university hospital. Methods We conducted a retrospective observational study in a tertiary care university ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have identified factors associated with cardiopulmonary arrest in critically ill children. Previous studies have demonstrated ST-segment variability, vasoactive-inotrope score, higher inadequate oxygen delivery index, venous saturation, serum lactate, cerebral dysfunction by electroencephalography, a history of a previous cardiac arrest, specific cardiac lesions, and specific cardiac surgeries among others[ 3 4 5 6 7 8 9 10 11 12 13 14 15 16 ] as risk factors for adverse outcomes. Risk factors for mortality have often mirrored the risk factors for cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified factors associated with cardiopulmonary arrest in critically ill children. Previous studies have demonstrated ST-segment variability, vasoactive-inotrope score, higher inadequate oxygen delivery index, venous saturation, serum lactate, cerebral dysfunction by electroencephalography, a history of a previous cardiac arrest, specific cardiac lesions, and specific cardiac surgeries among others[ 3 4 5 6 7 8 9 10 11 12 13 14 15 16 ] as risk factors for adverse outcomes. Risk factors for mortality have often mirrored the risk factors for cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate in children that underwent congenital heart surgery has steadily increased in the past several decades due to technological developments and appropriate postoperative care to the point that the perioperative mortality rate has decreased below 5%. However, major adverse events (MAEs), which develop unexpectedly and adversely affect surgical outcomes, continue to be a major concern (2). MAEs include sudden cardiac arrest/death, unscheduled emergency re-operation, and low cardiac output syndrome (LCOS).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of CHDs and many different complications that may develop after congenital heart surgeries pose serious difficulties in managing the patients and making the right decision about the treatment approach to be adopted. To overcome these difficulties, different methods are employed, including physical examination, non-invasive/invasive hemodynamic measurements, scoring systems, measurement of cerebral oxygen saturation levels by near-infrared spectroscopy (NIRS-ScO2), and measurement of lactate and mixed venous blood oxygen saturation (MVO) levels (2)(3)(4). Serum lactate, MVO, and NIRS-ScO2 levels are used as indirect markers secondary to tissue hypoxia, which is used to assess the insufficiency of oxygen transport to the periphery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting score had an area under the curve of 0.84 with an optimal Previous studies have identi ed factors associated with cardiopulmonary arrest in critically ill children. Previous studies have demonstrated ST-segment variability, vasoinotrope score, higher inadequate oxygen delivery index, venous saturation, serum lactate, cerebral dysfunction by electroencephalography, a history of a previous cardiac arrest, speci c cardiac lesions, and speci c cardiac surgeries among others[3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Risk factors for mortality have often mirrored the risk factors for cardiac arrest.…”
mentioning
confidence: 99%